2016
DOI: 10.1080/15397734.2015.1116996
|View full text |Cite
|
Sign up to set email alerts
|

Static lateral stiffness of wire rope isolators

Abstract: This paper presents an analytical model for the static lateral stiffness of Wire Rope Isolators (WRI). The wire rope isolator, which is a passive isolation device, has been widely adopted as a shock and vibration isolation for many types of equipment and lightweight structures. The major advantage of the WRI is its ability to provide isolation in all three planes and in any orientation. The WRI in the lateral roll mode, is required to possess the required lateral stiffness to support and isolate the equipment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…This hysteresis is a natural way, available in mechanical and structural systems, to provide restoring forces against movements and dissipate energy. Previous studies [ 3 , 4 , 6 , 7 , 8 , 9 ] have verified and confirmed that the WRI exhibits a hysteresis curve under cyclic loading and is due to the frictional resistance between the wire strands [ 10 ]. The studies [ 11 , 12 , 13 ] also shows that dry friction in the wire rope can cause energy dissipation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This hysteresis is a natural way, available in mechanical and structural systems, to provide restoring forces against movements and dissipate energy. Previous studies [ 3 , 4 , 6 , 7 , 8 , 9 ] have verified and confirmed that the WRI exhibits a hysteresis curve under cyclic loading and is due to the frictional resistance between the wire strands [ 10 ]. The studies [ 11 , 12 , 13 ] also shows that dry friction in the wire rope can cause energy dissipation.…”
Section: Introductionmentioning
confidence: 86%
“…The nonlinear elastic region is where the isolator behaves nonlinearly when subjected to large displacement amplitudes or when loaded in a specific direction. Many studies have observed this behavior [ 3 , 4 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 94%
“…An important characteristic of wire rope isolators is that it has the ability to isolate vibration in all directions, so it can be used in any direction to safeguard the structure and equipment. 810 However, it is difficult to satisfy various requirements of vibration isolation by adjusting the parameters of wire rope isolator.…”
Section: Introductionmentioning
confidence: 99%
“…It can be mounted in any orientation to protect structures and equipment excited in any direction. 11 Therefore, it can isolate the vertical vibration and ensure the horizontal safety at the same time, and its intrinsic damping can dissipate the vibration energy greatly. However, the wire rope isolator is installed in the vibration isolation system located between the fixed device and the excitation, thus it is difficult to adjust it in real time to adapt to different vibration isolation requirements or transportation conditions.…”
Section: Introductionmentioning
confidence: 99%